Change of Tumor Cell Multiple Drug Resistance Inhibitory Activity of Oligomycins in Complexes with Lithium and Zinc - M. V. Bibikova; A. N. Danilenko; A. V. Katlinsky; A. F. Korystova; L. N. Kublik; M. Kh. Levitman; V. V. Shaposhnikova; Yu. N. Korystov (Антибиотики и Химиотерапия, 2020)
Oligomycins and their complexes with lithium and zinc were shown to be less active vs. cyclosporin A in inhibition of transport proteins responsible for multiple drug resistance of lymphoid leukosis P388VR cells, while certain oligomycin complexes were tens or hundreds times more active than cyclosporin A by inhibition of transport proteins in another type of tumor cells, i.e. human larynx cancer Hep-2, that makes possible the use of the oligomycins complexes with lithium and zinc for inhibition of multiple drug resistance of certain tumor types.